USING DEBATE ACTIVITIES TO DEVELOP INDONESIAN HIGH SCHOOL STUDENTSâ SPEAKING SKILLS - Wulandari, Astri; Ena, Ouda Teda (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2018)
This research explores the use of debate activities which are implemented in an Indonesian high school. The aim of this research was to find out studentsâ perception on the use of debate activities in improving studentsâ speaking skills. The participants of this research were eight students participating in a debate extracurricular club in a public school. It was a descriptive-qualitative research. The data were collected through observations, questionnaires, and interviews. There were three observations in the debate activities. After that, the researchers distributed the questionnaires to the students. Interviews were conducted with eight students. The research result showed that debate activities enriched studentsâ vocabulary, improved studentsâ confidence, and helped students to become better public speakers.DOI : doi.org/10.24071/llt.2018.Suppl2102